2015
DOI: 10.1590/1807-1929/agriambi.v19n1p52-57
|View full text |Cite
|
Sign up to set email alerts
|

Produção da mamoneira submetida a combinações com fontes de fósforo e calagem

Abstract: R E S U M OA mamoneira é considerada cultura exigente em fósforo haja vista que a nutrição fosfatada adequada com a utilização de fontes solúveis em conjunto com fontes naturais, pode aumentar a eficiência de absorção do fósforo e a produtividade de mamona. Objetivou-se avaliar os componentes de produção da mamoneira após a combinação de adubações com fosfato solúvel e natural, na ausência e na presença de calagem. O estudo foi conduzido em esquema fatorial 2 x 5 envolvendo duas doses de calcário (com e sem ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In relation to the total number of fruits per plant (two racemes) (Figure 2E), the phosphate fertilization caused a quadratic effect, with maximum number of 78.90 fruits, at 581.33 kg ha -1 . Moreira et al (2012) reported average values of 27.9 fruits per raceme, in a study with the castor bean cultivar IAC Guarani as a function of phosphorus and boron, while several types of combination of fertilizations with soluble and natural phosphate had a significant effect on the number of fruits of the cultivar BRS Paraguaçu, which produced 142 fruits per plant and on average, 28.4 fruits in each raceme (Silveira et al, 2015). However, the different doses of phosphate fertilizer did not promote a significant effect on the number of fruits per plant in the cultivar Al Guarany 2002, producing 105 seeds with all treatments (Silva et al, 2013).…”
Section: G Hmentioning
confidence: 99%
“…In relation to the total number of fruits per plant (two racemes) (Figure 2E), the phosphate fertilization caused a quadratic effect, with maximum number of 78.90 fruits, at 581.33 kg ha -1 . Moreira et al (2012) reported average values of 27.9 fruits per raceme, in a study with the castor bean cultivar IAC Guarani as a function of phosphorus and boron, while several types of combination of fertilizations with soluble and natural phosphate had a significant effect on the number of fruits of the cultivar BRS Paraguaçu, which produced 142 fruits per plant and on average, 28.4 fruits in each raceme (Silveira et al, 2015). However, the different doses of phosphate fertilizer did not promote a significant effect on the number of fruits per plant in the cultivar Al Guarany 2002, producing 105 seeds with all treatments (Silva et al, 2013).…”
Section: G Hmentioning
confidence: 99%
“…Phosphorus is classified as macronutrients, and without it the plant fails to develop properly. This nutrient provides a favorable environment for roots development, besides providing other nutrients in smaller proportion such as sulfur, calcium and magnesium, that according to phosphorus source used (Lima et al, 2011;Silveira et al, 2015). Their absorption is by diffusion, action in those roots find during its growth (Elz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Alcantra Neto et al (2010) verified that the maintenance of soil phosphorus provides better final yield crop. This element is a component of nucleic acids and is directly related to photosynthesis and metabolic processes, as well as other benefits, such as the availability of calcium, magnesium and sulfur (Hippler et al, 2011;Silveira et al, 2015). Alcantra Neto et al (2010) note that consistent maintenance of phosphorus in the soil ensures the cultivation and significant progress in final production, as well as in helping to absorb water and other nutrients, providing resistance to cold and some diseases.…”
Section: Introductionmentioning
confidence: 99%